The Effect of Active Treatment and Visit Compared to Conventional Treatment, on Preventing Recurrent Suicidal Attempts: A Randomized Controlled Clinical Trial - Mousavi, Seyed Ghafur (Adv Biomed Res, 2017)
BACKGROUND: Suicide is a major problem, and its prevention is a global priority. In many cases, suicide attempter attempts to do it again after the rescue. In current study we aimed to compare active visit and treatment of patients in a periodic manner with treatment as usual, in the prevention of recurrent suicidal attempts. MATERIALS AND METHODS: This study was a randomized controlled clinical trial which was conducted in Isfahan Noor Hospital's Emergency Center on 60 patients in 2013-2014. The samples were selected using simple random sampling and they were assigned into two groups: The conventional treatment group (treatment as usual) (30 patients), and visit and active treatment (30 patients). In the intervention group, there were ten follow-ups by a face-to-face visit over 12 months, and six follow-ups by phone call in control group. Through the completion of the initial and follow-up questionnaire evaluation was performed. The data were analyzed using Cochran test, and repeated measure (ANOVA). RESULTS: During the 12-month follow-up visit and active treatment, significant difference in reducing suicidal thoughts (P = 0.003) was observed and an increase in the life expectancy (P = 0.001), interest and motivation in life (P = 0.001) was found in the intervention group, and also nonsignificant reduction was found in the rate of suicidal attempts. CONCLUSION: Visit and active treatment is useful in suicide attempters and it can helps in preventing recurrent suicide attempt as a preventive program by increasing hope and reducing suicidal thoughts.